Hardening assistant solution, self-hardening material, hardened body, and manufacturing method thereof
The curing aid solution with a high Si element and alkali concentration stabilizes the dissolution concentration of Si elements, addressing the challenges of achieving high strength and stability in self-hardening materials, and resulting in improved compressive strength and reduced shape change in the cured bodies.
Patent Information
- Application Number
- JP2020092393
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-05-27
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2040-05-27
AI Technical Summary
Existing self-hardening materials, such as those containing ceramic powders with Si elements, face challenges in achieving high strength and quality stability in their cured bodies, particularly due to variations in the dissolution concentration of Si elements over time.
A curing aid solution is developed that includes Si elements, alkali, and a dispersion medium with a dissolution concentration of Si elements at 20,000 ppm or more by mass and an alkali concentration of 2 mol/kg or more. This solution is designed to maintain a stable dissolution concentration of Si elements after heating and dilution, ensuring uniform composition and properties in the cured body.
The proposed curing aid solution effectively enhances the strength and stability of the cured body by maintaining a consistent Si element concentration, leading to improved compressive strength and reduced shape change, thereby addressing the limitations of existing self-hardening materials.
Smart Images

Figure 0007654213000001 
Figure 0007654213000002 
Figure 0007654213000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to a curing aid solution, a self-hardening material, a hardened body, and methods for producing the same. [Background technology]
[0002] Cementitious materials such as ordinary Portland cement are widely used as self-hardening materials for cement paste, mortar, and concrete. Cement clinker, the raw material for cement in cementitious materials, is produced by burning limestone and clay. Carbon dioxide is released during the burning of limestone and during the combustion of heavy fuel oil. It is estimated that one ton of carbon dioxide is generated per ton of cement clinker. In recent years, global warming has become a global issue, and regulating carbon dioxide emissions has become an important issue. Furthermore, these cementitious materials produce calcium hydroxide through hydration during hardening. Therefore, when cementitious materials are used to construct underground facilities such as storage facilities, water that comes into contact with the hardened cementitious material exhibits alkaline properties. However, when bentonite is used as a water-stopping material, there are concerns about its deterioration in alkaline environments. Similar concerns also exist regarding the surrounding bedrock. These issues necessitate the development of new alternative technologies to cementitious materials.
[0003] One of the alternative materials for cementitious materials is a self-hardening material containing a ceramic powder containing elemental silicon. Among such self-hardening materials, a mixture of a ceramic powder containing elemental silicon at least on its surface and a solution containing alkali and silicon powder, which can be used as a hardening aid solution, has been studied from the viewpoint of excellent density and strength.
[0004] Patent Document 1 discloses a method for producing a self-hardening material, which includes mixing fly ash whose surface has been activated by mechanochemical treatment with a silicon mixture obtained by mixing a strong alkaline solution with silicon powder, in which the silicon component has been eluted in the strong alkaline solution.The patent document also discloses that this production method provides a self-hardening material that can produce a highly dense hardened body.
[0005] Patent Document 2 discloses a method for producing a hardened body, which involves mixing fly ash with a slurry obtained by mixing a 3 mol / L potassium hydroxide solution with a specific silicon powder to obtain a mixture, and then hardening the mixture. It also discloses that this production method produces a hardened body with high strength. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Laid-Open No. 2015-218070 [Patent Document 2] Japanese Patent Application Laid-Open No. 2016-222528 Summary of the Invention [Problem to be solved by the invention]
[0007] Although the hardened body of the self-hardening material obtained by the manufacturing method according to Patent Document 1 and the hardened body manufactured by the manufacturing method according to Patent Document 2 have excellent strength, in recent years there has been an increasing demand for hardened bodies with even higher strength, and at the same time there has also been an increasing demand for higher quality stability than ever before.
[0008] Therefore, an object of the present invention is to provide a means for imparting high stability over time to a curing aid solution, which is the raw material for a hardened body of a self-hardening material containing a ceramic powder containing Si element at least on the surface, and for imparting high strength and high quality stability to the hardened body of the self-hardening material. [Means for solving the problem]
[0009] The above-mentioned problems of the present invention can be solved by the following means.
[0010] Contains Si element, alkali, and a dispersion medium, the dispersion medium comprises water, The dissolved concentration of the Si element is 20,000 ppm by mass or more, the number of moles of the alkali present in 1 kg of the dispersion medium is 2 mol / kg or more, The solution is diluted twice by mass with a 3 mol / L KOH aqueous solution, heated at 80°C for 5 hours, and then left to stand in an ambient environment at 25°C for 1 hour. The absolute value of the change in the dissolved concentration of Si element before and after the heat dissolution test is 2000 mass ppm or less. A curing aid solution used to harden a powder containing a ceramic powder containing Si element at least on the surface. [Effects of the Invention]
[0011] According to the present invention, there is provided a means for imparting high stability over time to a curing aid solution, which is the raw material for a hardened body of a self-hardening material containing a ceramic powder containing Si element at least on the surface, and for imparting high strength and high quality stability to the hardened body of the self-hardening material. DETAILED DESCRIPTION OF THE INVENTION
[0012] The present invention will be described below, but it should be noted that the present invention is not limited to the following embodiments.
[0013] In this specification, the range "X to Y" means "X or more and Y or less." Unless otherwise specified, operations and measurements of physical properties are carried out at room temperature (20 to 25°C) and a relative humidity of 40 to 50% RH.
[0014] One aspect of the present invention relates to a curing aid solution used to harden a powder containing a ceramic powder containing Si element at least on the surface thereof, the curing aid solution comprising: Si element, an alkali, and a dispersing medium, the dispersing medium containing water; the dissolved concentration of the Si element is 20,000 ppm by mass or more; the molar number of the alkali present in 1 kg of the dispersing medium is 2 mol / kg or more; and a solution diluted two-fold by mass with a 3 mol / L aqueous KOH solution is heated at a liquid temperature of 80°C for 5 hours and then allowed to stand in an ambient environment at 25°C for 1 hour. The absolute value of the change in the dissolved concentration of the Si element before and after a heat dissolution test is 2,000 ppm by mass or less.
[0015] The present inventors presume that the mechanism by which the above-mentioned problems are solved by the present invention is as follows.
[0016] In the past, in a curing aid solution containing a compound containing Si and an alkali, residual Si-containing compound remained, and the concentration of dissolved Si in the curing aid solution varied depending on the mixing time during preparation of the curing aid solution and the time between preparation of the curing aid solution and mixing with the object to be cured. Therefore, unless the conditions for preparing the curing aid solution and mixing with the object to be cured were strictly controlled, it was impossible to maintain a consistent strength of the cured body of the self-hardening material, making it difficult to obtain a cured body with high strength and high quality stability. On the other hand, the curing aid solution according to the present invention has a dissolved Si concentration of 20,000 ppm by mass or more and a molar number of alkali present per kg of dispersion medium of 2 mol / kg or more. The alkali concentration within this range further promotes dissolution of the compound containing Si in the curing aid solution, thereby further increasing the amount of dissolved Si and further suppressing the occurrence of residual Si-containing compound in the curing aid solution. This improves the stability over time of the curing aid solution and the self-hardening material containing it, making it possible to produce cured products with consistent strength, and suppresses the production of cured products with inferior strength, resulting in cured products with higher quality stability and strength.
[0017] Furthermore, when the concentration of dissolved Si element is within the above range, the amount of Si element in the curing aid solution is sufficient, further enhancing its function as a curing aid. In addition, in a self-hardening material having a predetermined alkalinity, the reaction involving these Si elements between the Si element on the surface of the ceramic powder and the Si element eluted from the curing aid solution proceeds sufficiently, and the curing of the ceramic powder proceeds, resulting in a cured body with higher strength.
[0018] In addition, if residual Si-containing compounds remain in a conventional curing aid solution, they settle, resulting in non-uniform distribution of the curing aid in the curing aid solution and in the self-hardening material containing the same. Furthermore, leaching from the residual Si compounds results in variations in the concentration of the Si-containing compounds in the curing aid solution over time. This variation in the composition of the self-hardening material and its hardened body varies depending on the location and time, leading to non-uniformity in the strength and other qualities of the material, making it difficult to obtain a hardened body with high strength and stable quality. In contrast, the curing aid solution of the present invention shows a change in the absolute value of the concentration of Si dissolved in the curing aid solution of 2000 ppm by mass or less before and after a heat dissolution test in which a solution obtained by diluting the solution twice by mass with a 3 mol / L KOH aqueous solution (diluted with an alkaline aqueous solution) is heated at 80°C for 5 hours and then allowed to stand at 25°C for 1 hour. The absolute value of the change in the dissolution concentration of Si element before and after the heat dissolution test within the above range indicates that the dissolution concentration of Si element does not substantially change even when the solution is heated under conditions in which the Si-containing compound is soluble. In other words, the absolute value of the change in the dissolution concentration of Si element before and after the heat dissolution test within the above range indicates that there is substantially no residual Si-containing compound in the hardening aid solution. In this case, the dissolution concentration of Si element remains constant regardless of time. Therefore, the composition of the self-hardening material and its hardened body becomes uniform, the uniformity of physical properties such as the strength of the hardened body is improved, strength variation is suppressed, and the production of hardened bodies with poor strength is also suppressed, resulting in hardened bodies with high strength and higher quality stability.
[0019] In addition, since the curing aid solution according to the present invention does not contain any undissolved compound containing Si element, excess raw material (compound containing Si element) is not required when preparing the solution, which can reduce costs.
[0020] The above mechanism is based on speculation, and its correctness does not affect the technical scope of the present invention. Similarly, the correctness of other speculations in this specification does not affect the technical scope of the present invention.
[0021] <Curing aid solution> (dissolved concentration of Si element) The hardening assistant solution according to one embodiment of the present invention contains elemental Si. The elemental Si dissolved in the hardening assistant solution promotes hardening of the ceramic powder by a reaction with the elemental Si of the ceramic powder containing elemental Si at least on the surface thereof, thereby contributing to the formation of a hardened body.
[0022] In the curing aid solution according to one embodiment of the present invention, the dissolved concentration of Si element is 20,000 ppm by mass or more. If the dissolved concentration of Si element is less than 20,000 ppm by mass, the hardened body of the self-hardening material will not have sufficient strength. This is presumably because the amount of Si element in the curing aid solution is insufficient, preventing the hardening aid from fully functioning. The dissolved concentration of Si element is more preferably 30,000 ppm by mass or more. If the dissolved concentration of Si element is within the above range, the hardening ability of the curing agent and the strength of the hardened body of the self-hardening material will be further improved. Furthermore, the dissolved concentration of Si element is preferably 120,000 ppm by mass or less. If the dissolved concentration of Si element is within the above range, the viscosity of the aid itself will be further prevented from becoming excessively high, and the occurrence of gelation, which is inappropriate for use, will be further suppressed.
[0023] From the viewpoint of the strength of the cured body, the dissolved concentration of Si element is more preferably 35,000 mass ppm or more, even more preferably 40,000 mass ppm or more, particularly preferably 70,000 mass ppm or more, and most preferably 90,000 mass ppm or more.
[0024] From the viewpoint of the rate of change in shape of the cured body, the concentration of dissolved Si element is more preferably 100,000 ppm by mass or less, further preferably 50,000 ppm by mass or less, and particularly preferably 35,000 ppm by mass or less.
[0025] The concentration of dissolved Si element in the hardening aid solution can be controlled by the amount of Si element-containing compound used as the raw material for dissolution, the amount of alkali added which is related to the solubility of Si element, and the pH value. For example, the concentration of dissolved Si element can be increased by increasing the amount of Si element-containing compound used, the amount of alkali added, and the pH value.
[0026] Furthermore, in a curing aid solution according to one embodiment of the present invention, the curing aid solution is diluted 2-fold by mass with a 3 mol / L KOH aqueous solution (diluted with an alkaline aqueous solution), heated at 80°C for 5 hours, and then allowed to stand for 1 hour in an ambient environment at 25°C. The absolute change in the dissolved silicon concentration before and after a heat dissolution test is 2000 ppm by mass or less (lower limit: 0 ppm by mass). If the absolute change exceeds 2000 ppm by mass, the dissolved silicon concentration changes over time, resulting in insufficient stability over time and compositional uniformity of the curing aid solution and self-hardening material, resulting in insufficient quality stability and strength of the cured product. This is presumably because, when the absolute change exceeds 2000 ppm by mass, the compound containing silicon is not completely dissolved in the curing aid solution, leaving residual silicon. In this case, the silicon continues to leach from the compound containing silicon in the form of silicate ions, etc.
[0027] In the curing aid solution according to one embodiment of the present invention, even if residual Si-containing compounds remain, there is no case in which the absolute value of the change in the dissolved Si concentration in the curing aid solution diluted with alkali before and after the thermal dissolution test is 2000 mass ppm or less. If residual Si-containing compounds remain in the curing aid solution, the state in which these residual compounds remain is no longer in equilibrium upon dilution with a 3 mol / L KOH aqueous solution in the thermal dissolution test, i.e., upon addition of alkali. Therefore, subsequent heating causes the concentration of this diluted curing aid solution to change.
[0028] The absolute value of the change in the dissolved concentration of Si element before and after the heat dissolution test can be reduced by adding a sufficient amount of alkali to the amount of Si-containing compound used as the raw material for dissolution so that no undissolved alkali remains, and to achieve a sufficient concentration.
[0029] The dissolution concentration of Si element can be measured as follows. The solution to be measured (e.g., a curing aid solution or a diluted curing aid solution) is centrifuged at 81769 G for 30 minutes using a centrifuge (Avanti HP-301, manufactured by Beckman Coulter, Inc.), and the supernatant is separated. The separated supernatant is then diluted with pure water at a predetermined ratio and subjected to inductively coupled plasma emission spectrometry using an inductively coupled plasma optical emission spectrometer (SPS3510, manufactured by Hitachi High-Tech Science Corporation). The dissolved Si element concentration (ppm by mass) of the diluted supernatant is measured based on a calibration curve prepared using a silicon standard stock solution (manufactured by Kanto Chemical Co., Inc.). The product of the obtained value and the dilution ratio of the supernatant with pure water by mass is then used to evaluate the dissolved Si element concentration. The dilution ratio of the supernatant with pure water by mass is not particularly limited, but can be, for example, 2000 times. Details of the method for evaluating the dissolved Si element concentration and the details of the heating test are described in the Examples.
[0030] In the present invention, the state of the Si element dissolved in the curing aid solution is not particularly limited, and may be, for example, in the form of silicate ions.
[0031] The Q3 ratio of silicate ions in the curing aid solution according to one embodiment of the present invention is not particularly limited, but is preferably 45% or less (lower limit: 0%). The Q3 ratio (%) is expressed as the ratio of the area of the peak (Q3) derived from a Si element in which three of the O elements of an SiO4 tetrahedron are shared by adjacent Si elements (i.e., a peak derived from a Si-(OH)1 structure) to the total area of the peaks derived from the Si element in which three of the O elements of the SiO4 tetrahedron are shared by adjacent Si elements (Q4), the peak (Q3) derived from a Si element in which three of the O elements of the SiO4 tetrahedron are shared by adjacent Si elements (Q2), the peak (Q1) derived from a Si element in which one of the O elements of the SiO4 tetrahedron is shared by adjacent Si elements (Q1), and the peak (Q0) derived from a Si element in which none of the O elements of the SiO4 tetrahedron are shared by adjacent Si elements. When the Q3 ratio is within the above range, the shape change rate of the hardened body of the self-hardening material containing the hardening assistant solution, particularly the shape change rate of the hardened body of the self-hardening material containing a large amount of water, is further reduced.
[0032] The peak areas of Q0 to Q4 used to calculate the Q3 ratio of silicate ions can be measured as follows: The hardening aid solution was subjected to liquid NMR analysis using a superconducting high-resolution nuclear magnetic resonance spectrometer (ECZ700R manufactured by JEOL RESONANCE) under the conditions of Offset: -90 ppm, Sweep: 40 ppm, Points: 4096, Scans: 256, and Relaxation: 120 s. 29 The Si NMR is measured. Details of the method for evaluating the Q3 ratio of silicate ions are described in the Examples.
[0033] The source of elemental Si dissolved in the curing aid solution, i.e., the Si-containing compound used as the raw material, is not particularly limited as long as it can provide dissolved elemental Si in the presence of an alkali, as described below. Examples include silicon element, silicon-containing oxides, nitrides, carbides, oxynitrides, carbides nitrides, and carbides nitrides. These are preferably in powder form. Therefore, preferred compounds containing elemental Si include silicon oxide (silica) powder, silicon nitride powder, silicon carbide powder, silicon oxynitride powder, silicon carbonitride powder, and polysilicon powder. Other examples include silicic acids such as orthosilicic acid, pyrosilicate, metasilicic acid, and metadisilicate, as well as silicates such as potassium silicate (K2SiO3) and sodium silicate (Na2SiO3). Among these, silica or elemental silicon is preferred, amorphous silica is more preferred, and silica fume, primarily composed of amorphous silica, is even more preferred. The use of these preferred Si-containing compounds improves the stability over time and the uniformity of the composition of the curing aid solution and the self-hardening material, thereby improving the quality stability and strength of the hardened product. Furthermore, the use of amorphous silica powder improves the shape change rate of the hardened product of the self-hardening material, especially for self-hardening materials containing a large amount of water.
[0034] Furthermore, it is preferable that the compound containing Si element does not contain alkali metal silicate or Group 2 metal silicate, which further improves the shape change rate of the hardened body of the self-hardening material, especially the shape change rate of the hardened body of the self-hardening material containing a large amount of water.
[0035] The Si-containing compound may be a commercially available product or a synthetic product, such as Elkem Microsilica 940U manufactured by Elkem Japan Co., Ltd., which is a silica fume powder that is an amorphous silica powder mainly composed of amorphous silica.
[0036] The compounds containing Si element can be used alone or in combination of two or more kinds.
[0037] It is believed that in the curing aid solution according to one embodiment of the present invention, all of the compounds containing the Si element are dissolved, and no powdery particles or other substances, i.e., no undissolved residues, are present.
[0038] (alkali) The curing aid solution according to one embodiment of the present invention contains an alkali. The alkali refers to a compound that, when added to the curing aid solution, increases the pH of the solution. The alkali contributes to sufficiently dissolving the compound containing Si element in the curing aid solution.
[0039] In one embodiment of the hardening aid solution, the number of moles of alkali present in 1 kg of dispersion medium (hereinafter also referred to as the "alkali molar concentration") is 2 mol / kg or more. If the alkali molar concentration is less than 2 mol / kg, the hardened body of the self-hardening material will not have sufficient strength. This is presumably because the Si-containing compound, which is the raw material of the hardening aid solution, is not sufficiently dissolved in the hardening aid solution, preventing the Si element from being fully eluted, thereby preventing the hardening aid from fully functioning. Furthermore, this is presumably because the amount of undissolved Si-containing compound increases significantly, causing the Si element to continuously elute from this undissolved compound in the form of silicate ions, etc., resulting in a change in the dissolved Si element concentration over time, which in turn reduces the stability over time and uniformity of the composition of the hardening aid solution and the self-hardening material, thereby reducing the quality stability and strength of the hardened body. The lower limit of the alkali molar concentration is preferably 2.5 mol / kg or more, and more preferably 3 mol / kg or more. Within this range, the stability over time and uniformity of the composition of the hardening aid solution and the self-hardening material are further improved, and the quality stability and strength of the hardened body are also further improved. The upper limit of the alkali molar concentration is not particularly limited, but is preferably 8 mol / kg or less, and more preferably 6 mol / kg or less. Within this range, the safety of the curing aid solution and the self-hardening material containing it is further improved.
[0040] In this specification, the term "molar concentration of alkali" refers to the number of moles of alkali present in 1 kg of dispersion medium. The molar concentration of alkali in a curing aid solution can be calculated by measuring the concentration of alkali metal ions in the curing aid solution using inductively coupled plasma atomic emission spectrometry or the like, converting the result into the number of moles of alkali metal ions per kg of the curing aid solution, and then dividing this value by the mass fraction of the dispersion medium in the curing aid solution, calculated from the mass loss upon evaporative drying. Furthermore, when the formulation of the curing aid solution is simple, the molar concentration of alkali in the curing aid solution can also be calculated by calculating the number of moles of alkali (mol / kg) present in 1 kg of dispersion medium from the number of moles or mass of alkali used, the mass of the dispersion medium, and the molecular weight (g / mol) of the alkali. The molar concentration of alkali in a curing aid solution can also be calculated by centrifuging the curing aid solution, separating the supernatant, adding methyl orange indicator to the separated supernatant, and titrating with hydrochloric acid to determine the amount used.
[0041] The alkali is not particularly limited, and known alkalis can be used. Examples include hydroxides of alkali metals or Group 2 metals. Examples of alkali metal hydroxides include potassium hydroxide and sodium hydroxide. Examples of Group 2 metal hydroxides include magnesium hydroxide and calcium hydroxide. Among these, the alkali is preferably a hydroxide of an alkali metal, more preferably potassium hydroxide or sodium hydroxide, and particularly preferably potassium hydroxide. The use of these preferred alkalis further improves the stability over time and uniformity of the composition of the curing aid solution and the self-hardening material, and further improves the quality stability and strength of the cured product.
[0042] The alkali may be a commercially available product or a synthetic product.
[0043] The alkalis can be used alone or in combination of two or more kinds.
[0044] (dispersion medium) The curing aid solution according to one embodiment of the present invention contains a dispersion medium, which disperses or dissolves each component.
[0045] The dispersion medium contains water. Water exhibits alkalinity by dissolving alkalis, which contributes to dissolving compounds containing Si element. The water preferably contains as few impurities as possible. For example, water having a total transition metal ion content of 100 ppb or less is preferred. Here, the purity of the water can be increased by, for example, removing impurity ions using an ion exchange resin, removing foreign matter using a filter, or by distillation. Specifically, it is preferred to use, for example, deionized water (ion-exchanged water), pure water, ultrapure water, distilled water, etc. as water.
[0046] The dispersion medium other than water may be an organic solvent for dispersing or dissolving each component. In this case, preferred examples of the organic solvent used include acetone, acetonitrile, ethanol, methanol, isopropanol, glycerin, ethylene glycol, propylene glycol, and the like, which are organic solvents miscible with water. Alternatively, the organic solvent may be used without mixing with water, and then each component may be dispersed or dissolved therein, and then mixed with water. These organic solvents may be used alone or in combination of two or more.
[0047] Here, the content of water in the dispersion medium is preferably 50% by mass or more, more preferably 80% by mass or more, and even more preferably 100% by mass (water only) relative to the total mass of the dispersion medium (upper limit 100% by mass).
[0048] (Method of manufacturing hardening aid solution) The method for producing the curing aid solution is not particularly limited, and any known method can be used. Among these, a method including mixing a compound containing Si element with an alkaline solution containing water and having an alkali molar ratio of 2 mol / kg or more in 1 kg of dispersion medium to obtain a mixed solution is preferred.
[0049] Here, the compound containing Si element, the alkali, and the dispersion medium are as described above. As described above, the method for producing the curing aid solution preferably does not include mixing an alkali metal silicate or a Group 2 metal silicate as the compound containing Si element.
[0050] The mixing method, procedure, and device are not particularly limited, and known methods, procedures, and devices can be appropriately selected and used. The mixing device is not particularly limited, and any conventionally known mixer or kneader can be used. Examples include a double-arm kneader, a pressure kneader, an Eirich mixer, a super mixer, a planetary mixer, a Banbury mixer, a continuous mixer, and a continuous kneader. It is also preferable to use a vacuum kneader to remove air bubbles.
[0051] Furthermore, the manufacturing method according to this embodiment preferably includes heat-treating the mixed solution obtained. Heat-treating improves the temporal stability of the curing aid solution, and also improves the temporal stability and compositional uniformity of the self-hardening material, resulting in a cured product with higher quality stability and strength. It is presumed that this is because heat-treating further promotes the dissolution of the compound containing Si element in the curing aid solution, thereby further increasing the amount of Si element dissolved and further suppressing the occurrence of undissolved compounds containing Si element in the curing aid solution.
[0052] The heating method, procedure, and device are not particularly limited, and known methods, procedures, and devices can be appropriately selected and used.
[0053] Regarding the dissolution conditions, the heating temperature is preferably 50°C or higher, more preferably 60°C or higher, and even more preferably 80°C or higher. This is because the higher the temperature, the faster the dissolution rate of the Si-containing compound, allowing it to be dissolved in a shorter time. Furthermore, the heating temperature is preferably 100°C or lower, more preferably 95°C or lower, and even more preferably 90°C or lower. If the temperature is too high, the dispersion medium may volatilize during heating, making it impossible to obtain a curing aid solution of the desired concentration. The heating time is preferably 3 hours or longer, more preferably 4 hours or longer, and even more preferably 5 hours or longer. This is because heating for a certain period of time or longer ensures that the Si-containing compound is dissolved without any residue. Furthermore, the heating time is preferably 24 hours or shorter, more preferably 12 hours or shorter, and even more preferably 8 hours or shorter. If the dissolution time is too long, the dispersion medium may volatilize during heating, making it impossible to obtain a curing aid solution of the desired concentration. Therefore, it is preferable that the method for producing the curing aid solution further comprises heating the mixed solution at a liquid temperature of 80° C. or higher for 5 hours or more.
[0054] (Object to be hardened) The hardening assistant solution according to one embodiment of the present invention is used to harden a powder containing a ceramic powder containing Si element at least on its surface. The Si element dissolved in the hardening assistant solution reacts with the Si element of the ceramic powder containing Si element at least on its surface, and the hardening of the ceramic powder proceeds through a reaction involving these Si elements.
[0055] The ceramic powder containing Si element at least on the surface is not particularly limited, and known ceramic powders can be used. Among these, aluminosilicates and blast furnace slag are preferred, with aluminosilicates being more preferred. Examples of aluminosilicates include industrial wastes such as fly ash, red mud, silica fume, and sewage sludge incineration ash; natural aluminosilicate minerals and their calcined products (e.g., metakaolin); and volcanic ash. Among these, fly ash is preferred from the standpoints of availability and cost. Other ceramic powders, such as those described in paragraphs "0016" and "0017" of JP 2008-239433 A, may also be used.
[0056] The ceramic powder containing Si element at least on its surface preferably includes a ceramic powder containing Si element at least on its surface with an amorphized surface, more preferably an amorphized aluminosilicate or an amorphized blast furnace slag, even more preferably an amorphized aluminosilicate, and particularly preferably an amorphized fly ash. By amorphizing the surface, the surface is activated, increasing reactivity with the hardening aid solution and enhancing the strength of the hardened body of the self-hardening material. The network structure containing Si element exists in an amorphous state in the amorphous layer, making it susceptible to alkali corrosion, and making dissolution and reprecipitation of Si element in the amorphous layer more likely to occur. This is presumably because it also facilitates the reaction between Si element dissolved in the hardening aid solution and Si element of the ceramic powder containing Si element at least on its surface. The amorphization of the surface can be confirmed by observing a decrease in the crystalline peak intensity using X-ray diffraction, or by observing the atomic bonding state using X-ray electron spectroscopy or X-ray absorption fine structure analysis.
[0057] The ceramic powder containing Si element at least on the surface may be a commercially available product or a synthetic product.
[0058] The ceramic powder containing Si element at least on the surface thereof can be used alone or in combination of two or more kinds.
[0059] Furthermore, the powder containing ceramic powder containing Si element at least on its surface may contain other powders. It may also contain other components having a form other than powder. The content of the ceramic powder containing Si element at least on its surface relative to the total mass of the powder containing ceramic powder containing Si element at least on its surface is not particularly limited, but is preferably 60 mass% or more and 100 mass% or less.
[0060] As will be described later in the description of the self-hardening material, the calcium oxide (CaO) content (also referred to as "CaO content" in this specification) relative to the total mass of the powder including the ceramic powder containing Si element at least on the surface is not particularly limited, but is preferably 15 mass% or less (lower limit: 0 mass%).
[0061] <Self-hardening material> Another aspect of the present invention relates to a self-hardening material comprising the above-mentioned curing aid solution and a ceramic powder containing elemental Si at least on its surface. The self-hardening material has high stability over time and uniform composition, and the strength and quality stability of the hardened body obtained therefrom are also high.
[0062] The self-hardening material hardens through a reaction between the Si element dissolved in the hardening assistant solution and the Si element of the ceramic powder containing Si element at least on its surface. The ceramic powder containing Si element at least on its surface is as described above for the ceramic powder containing Si element at least on its surface in the description of the object to be hardened with the hardening assistant solution.
[0063] As long as the self-hardening material contains ceramic powder containing Si element at least on its surface, it may contain powder other than the ceramic powder containing Si element at least on its surface. In other words, this embodiment can also be said to relate to a self-hardening material containing the above-mentioned hardening aid solution and a powder containing ceramic powder containing Si element at least on its surface. In this case, it is preferable that the self-hardening material further contains aggregate other than the ceramic powder containing Si element at least on its surface as a powder. Such aggregate is not particularly limited, and known coarse aggregate or fine aggregate can be used.
[0064] The calcium oxide (CaO) content (CaO content) relative to the total mass of the powder containing ceramic powder containing Si element at least on its surface is not particularly limited, but is preferably 15 mass% or less (lower limit 0 mass%). That is, the self-hardening material preferably contains powder with a CaO content of 15 mass% or less, and the powder preferably contains the ceramic powder containing Si element at least on its surface. If the content is within the above range, a phenomenon similar to efflorescence, which is known to occur in cement due to Ca, is less likely to occur. The CaO content can be evaluated, for example, by fluorescent X-ray analysis.
[0065] The method for producing the self-hardening material is not particularly limited, and any known method can be used. Among these, a method including preparing the curing aid solution or producing a curing aid solution by the above-mentioned method for producing a curing aid solution, mechanochemically treating ceramic powder containing Si element at least on the surface, and mixing the prepared curing aid solution or the produced curing aid solution with the ceramic powder after the mechanochemical treatment is preferred.
[0066] Mechanochemical processing is a process that utilizes the high energy generated locally by mechanical energy such as friction and compression during the milling process of solid materials to induce chemical reactions such as crystallization, solid solution, and phase transition. When mechanochemical processing is performed on ceramic powders containing Si at least on their surface, the surface of the ceramic powder containing Si at least on its surface is activated. In other words, a ceramic powder containing Si at least on its surface is obtained with an amorphous surface. Surface activation by mechanochemical processing, i.e., amorphization of the surface, enhances reactivity with the hardening agent solution and increases the strength of the hardened body of the self-hardening material. The amorphous layer contains a network structure containing Si in an amorphous state, making it susceptible to alkali corrosion. This facilitates dissolution and reprecipitation of Si from the amorphous layer, which is thought to facilitate reactions between the Si dissolved in the hardening agent solution and the Si of the ceramic powder containing Si at least on its surface.
[0067] Mechanochemical treatment is effective when various forces such as impact, friction, compression, and shear are applied in combination. There are no particular limitations on the equipment capable of performing such actions, and known equipment can be used. Examples include mixing equipment such as ball mills, vibration mills, planetary ball mills, and media-agitated mills; grinders such as ball media mills, roller mills, and mortars; and jet grinders that can apply forces such as impact and grinding to the material to be ground. When a ball media mill is used, there are no particular limitations on the balls, and known equipment can be used. Examples include zirconia balls.
[0068] The mechanochemical treatment conditions are not limited, but it is preferable to continue until the particle size distribution no longer changes over time. By continuing the treatment until the particle size distribution no longer changes over time, it is believed that the ceramic powder containing Si element on the surface has reached the limit of its pulverization by grinding, and that the mechanochemical amorphization of the ceramic surface has reached its most advanced state. When using a ball media mill, the rotation speed of the ball media mill is generally not particularly limited as long as it can sufficiently apply energy to the powder, but is preferably 200 rpm or higher, and the upper limit is not particularly limited as long as it is below the upper limit of the equipment used. Furthermore, the stimulation time is not particularly limited, but is preferably 3 to 24 hours.
[0069] Here, the ceramic powder containing Si element at least on the surface is as described above for the ceramic powder containing Si element at least on the surface in the object to be cured with the curing assistant solution.
[0070] The amounts of ceramic powder containing Si element at least on its surface and curing aid solution used are preferably as follows: The mass of the dispersion medium (e.g., water) in the self-hardening material (hereinafter also referred to as W / B) relative to the total mass of the ceramic powder containing Si element at least on its surface in the self-hardening material and the Si-containing compound (e.g., amorphous silica or K2SiO3) used as a raw material for the curing aid solution (100 parts by mass) is preferably greater than 0 parts by mass, more preferably greater than 20 parts by mass, and even more preferably greater than 25 parts by mass. This range ensures that a sufficient amount of curing aid solution is added to the ceramic powder containing Si element at least on its surface, and that dissolved Si element in the curing aid is also sufficiently supplied. Furthermore, W / B is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, even more preferably 35 parts by mass or less, and particularly preferably 30 parts by mass or less. Within this range, the strength of the cured body is further improved and the rate of shape change of the cured body is further reduced.
[0071] However, from the viewpoint of more effectively utilizing the effect of reducing the shape change rate, W / B is preferably 30 parts by mass or more, more preferably 35 parts by mass or more, and even more preferably 40 parts by mass or more.
[0072] The method for producing the self-hardening material may include mixing the prepared hardening aid solution or the produced hardening aid solution with ceramic powder containing Si element at least on the surface after mechanochemical treatment (ceramic powder containing Si element at least on the surface, the surface of which has been made amorphous), and then further mixing with aggregate.
[0073] The aggregate is not particularly limited, and known coarse aggregate or fine aggregate can be used. The aggregate may be a ceramic powder containing Si element at least on its surface, or an aggregate other than a ceramic powder containing Si element at least on its surface. The ceramic powder containing Si element at least on its surface that can be used as the aggregate is as described above for the ceramic powder containing Si element at least on its surface in the object to be cured with the hardening aid solution. Furthermore, the aggregate other than the ceramic powder containing Si element at least on its surface is not particularly limited, and known coarse aggregate or fine aggregate that does not contain Si element on its surface can be used.
[0074] <Cured body> Another aspect of the present invention relates to a cured body, which is a cured product of the self-hardening material. The cured body has high strength.
[0075] The strength of the hardened body can be determined by evaluating its compressive strength. When the stability over time and uniformity of the composition of the hardening aid solution and the self-hardening material are high, and the effect of the hardening aid solution is also large, the hardened body can have a high compressive strength. The compressive strength of the hardened body is 8 N / mm 2 It is preferable that the resistance is 10N / mm or more. 2 More preferably, it is 24N / mm 2The compressive strength of the hardened body can be measured by a uniaxial compression test using a compression tester (Autograph AG-100KNX manufactured by Shimadzu Corporation). Details of the method for evaluating the compressive strength of the hardened body are described in the Examples.
[0076] The smaller the shape change of the hardened body, the better. That is, the smaller the absolute value of the shape change rate of the hardened body, the better. Preferably, it is 6% or less, more preferably 5% or less, even more preferably 2% or less, even more preferably 1% or less, particularly preferably 0.5% or less, and most preferably 0.1% or less (lower limit 0%). In particular, when the W / B of the self-hardening material is 40 parts by mass or more, it is preferable that the shape change rate be within the above range. The shape change rate of the hardened body can be calculated as follows: The diameter of the self-hardening material immediately after casting is measured using a vernier caliper. Next, after 48 hours of sealed curing at 40°C, the material is removed from the form and further dried and cured at 40°C for 5 days to obtain a hardened body. Next, the diameter of the obtained hardened body is measured using a vernier caliper. The shape change rate [%] is then calculated using the formula [(diameter of hardened body - diameter immediately after casting) / diameter immediately after casting] × 100. Details of the method for evaluating the shape change rate of the hardened body are described in the Examples.
[0077] The method for producing the cured body is not particularly limited, and any known method can be used. Among these, it is preferable that the method includes preparing the self-hardening material or producing a self-hardening material by the method for producing a self-hardening material, and curing the prepared or produced self-hardening material.
[0078] The curing method, procedure, and device are not particularly limited, and known methods, procedures, and devices can be appropriately selected and used.
[0079] The method for producing a hardened body preferably does not include heat curing the hardened self-hardening material at 50°C or higher. For example, the hardened body may be obtained by pouring the self-hardening material into a cylindrical formwork, sealing and curing it at 40°C for 48 hours, removing it from the formwork, and then dry curing it at 40°C for another 5 days to obtain a hardened body. In particular, when amorphous silica is used as a raw material for the hardening aid solution used in producing the self-hardening material and mechanochemical treatment is performed on ceramic powder containing Si element at least on the surface in the production of the self-hardening material, a hardened body having high strength and a small rate of shape change can be produced without heat curing the hardened self-hardening material at 50°C or higher. [Example]
[0080] The present invention will be described in more detail using the following examples and comparative examples. However, the technical scope of the present invention is not limited to the following examples. Unless otherwise specified, "%" and "parts" mean "% by mass" and "parts by mass", respectively.
[0081] <Curing aid solution> [Preparation of curing aid solutions 1 to 13] Each curing aid solution was prepared by adding the Si-containing compound (raw material) to the alkaline aqueous solution, mixing, and stirring the resulting mixture under specified dissolution conditions. The type of alkali, concentration of the alkaline aqueous solution, type of Si-containing compound, amount of alkaline aqueous solution and Si-containing compound used, and dissolution conditions used in preparing each curing aid solution are shown in Table 1 below.
[0082] As the amorphous silica in Table 1 below, silica fume powder (Elkem 940U, manufactured by Elkem Japan Co., Ltd.), which is a silica powder containing amorphous silica as the main component, was used.
[0083] In Table 1 below, the temperature in the dissolution conditions indicates the liquid temperature, and except for the preparation of curing aid solution No. 13, the liquid temperature was constant from the start of the reaction to the end of the reaction.
[0084] [Mass molarity of alkali in hardening aid solution] The number of moles of alkali [mol / kg] present in 1 kg of dispersion medium (water) was calculated from the amount of alkali used and the amount of dispersion medium (water).The number of moles of alkali [mol / kg] present in 1 kg of dispersion medium (water) can also be calculated by centrifuging the curing aid solution after preparation, separating the supernatant, adding methyl orange indicator to the separated supernatant, and titrating with hydrochloric acid to determine the amount used.
[0085] The evaluation results of the alkali molar concentration of the curing aid solution are shown in Table 2 below.
[0086] [Dissolved concentration of Si element] (1. Dissolved concentration of Si element in hardening aid solution) The curing aid solution prepared above was allowed to stand for 1 hour in an ambient environment at 25 ° C, and a portion of the curing aid solution was then separated. The separated curing aid solution was then centrifuged at 81769 G for 30 minutes using a centrifuge (Avanti HP-301, manufactured by Beckman Coulter) and the supernatant was separated. The supernatant was then diluted 2000 times by mass with pure water and subjected to inductively coupled plasma emission spectrometry using an inductively coupled plasma emission spectrometer (SPS3510, manufactured by Hitachi High-Tech Science Corporation). The dissolved silicon concentration (ppm by mass) of the 2000-fold diluted supernatant was measured using a calibration curve prepared using a silicon standard stock solution (manufactured by Kanto Chemical Co., Ltd.). The obtained value was then multiplied by 2000 to obtain the dissolved silicon concentration (ppm by mass).
[0087] (2. Absolute value of change in dissolved concentration of Si element before and after heating test) The prepared curing aid solution was left to stand for 1 hour in an ambient environment at 25°C, and then a portion of the curing aid solution was taken out. Next, this taken out curing aid solution was diluted twice by mass with a 3 mol / L KOH aqueous solution to prepare a diluted solution with an alkaline aqueous solution.
[0088] Next, the obtained diluted solution of the alkaline aqueous solution was centrifuged in the same manner as in the above-mentioned 1. Measurement of the dissolved concentration of Si element in the curing aid solution, and the supernatant was separated. Then, this supernatant was diluted 2000 times by mass with pure water, and inductively coupled plasma atomic emission spectrometry was performed in the same manner as in the above-mentioned 1. Measurement of the dissolved concentration of Si element in the curing aid solution. The obtained value was multiplied by 2000 to obtain the dissolved concentration of Si element [ppm by mass] before the heating test.
[0089] Furthermore, a thermal dissolution test was conducted on the diluted solution of the alkaline aqueous solution obtained above, in which the solution was heated at a temperature of 80°C for 5 hours and then allowed to stand in an ambient environment of 25°C for 1 hour. The diluted solution after the thermal dissolution test was centrifuged in the same manner as in 1. Measurement of the dissolved concentration of Si element in the curing aid solution above, and the supernatant was separated. This supernatant was then diluted 2000 times by mass with pure water, and inductively coupled plasma atomic emission spectrometry was performed in the same manner as in 1. Measurement of the dissolved concentration of Si element in the curing aid solution above. The obtained value was multiplied by 2000 to obtain the dissolved concentration of Si element [ppm by mass] after the heating test.
[0090] Then, the absolute value (ppm by mass) of the change in the dissolved concentration of Si element before and after the heating test was calculated from the values of the dissolved concentration of Si element before and after the heating test.
[0091] (3. Dissolved concentration of Si element in hardening aid solution after 24 hours) The prepared curing aid solution was allowed to stand for 24 hours in an ambient environment at 25°C, and then a portion of the curing aid solution was taken. The taken curing aid solution was then centrifuged in the same manner as in 1. Measurement of the dissolved Si element concentration in the curing aid solution, and the supernatant was taken. This supernatant was diluted 2000 times by mass with pure water and subjected to inductively coupled plasma atomic emission spectrometry. The obtained value was then multiplied by 2000 to obtain the dissolved Si element concentration [ppm by mass] before the heating test.
[0092] The evaluation results of the dissolution concentration of the Si element are shown in Table 2 below. Here, the results of the dissolution concentration of the Si element in the curing aid solution are shown in the column "Left to stand for 1 hour after preparation," and the results of the dissolution concentration of the Si element in the curing aid solution after 24 hours are shown in the column "Left to stand for 24 hours after preparation." Furthermore, for the dilution of the curing aid solution with an alkaline aqueous solution, the results of the dissolution concentration of the Si element before the heating test are shown in the column "Before heating test (dilution with alkaline aqueous solution)," and the results of the dissolution concentration of the Si element after the heating test are shown in the column "After heating test (dilution with alkaline aqueous solution)."
[0093] [Q3 ratio in NMR peak ratio (%)] The prepared curing aid solution was left to stand for 1 hour in an ambient environment at 25°C, and then a portion of the curing aid solution was taken. Next, the liquid phase of the taken curing aid solution was analyzed using a superconducting high-resolution nuclear magnetic resonance spectrometer (JEOL RESONANCE ECZ700R) under the following conditions: Offset: -90 ppm, Sweep: 40 ppm, Points: 4096, Scans: 256, Relaxation: 120 s. 29 Si NMR was measured.
[0094] From these results, the peak areas of the following were calculated: peak (Q4) derived from a Si element in which four of the O elements in the SiO4 tetrahedron are shared with adjacent Si elements; peak (Q3) derived from a Si element in which three of the O elements in the SiO4 tetrahedron are shared with adjacent Si elements; peak (Q2) derived from a Si element in which two of the O elements in the SiO4 tetrahedron are shared with adjacent Si elements; peak (Q1) derived from a Si element in which one of the O elements in the SiO4 tetrahedron is shared with adjacent Si elements; and peak (Q0) derived from a Si element in which none of the O elements in the SiO4 tetrahedron are shared with adjacent Si elements. The ratio of the area of the peak derived from a Si element in which three of the O elements in the SiO4 tetrahedron are shared with adjacent Si elements (i.e., the peak derived from the Si-(OH)1 structure) (Q3) to the total area of these peaks was defined as the Q3 rate (%).
[0095] In this measurement, the peak (Q4) due to the Si element, where all of the O elements in the SiO4 tetrahedron are shared by adjacent Si elements, was not observed (area 0), so the Q3 ratio was the same as the ratio of the Q3 value to the sum of Q0 to Q3.
[0096] The evaluation results of the Q3 rate of the curing aid solution are shown in Table 2 below.
[0097] [Table 1]
[0098] [Table 2]
[0099] <Self-hardening materials and their hardened bodies> [Preparation of Surface-Activated Fly Ash] 50 g of fly ash (average volume particle size 20 μm, CaO content: 10.1 mass% or less) was placed in a 500 mL zirconia pot, zirconia balls (diameter 10 mm) were added, and mechanochemical treatment was performed using a planetary ball mill (Fritsch P-5 type) at a rotation speed of 300 rpm for a stimulation time of 6 hours to obtain surface-activated fly ash, i.e., surface-amorphized fly ash (surface amorphized FA) (CaO content: 10.1 mass% or less).
[0100] [Preparation of self-hardening material using surface amorphized fly ash] Each self-hardening material was prepared by adding each of the curing aid solutions obtained above to the surface-amorphized FA obtained above and stirring the resulting mixture until a uniform mixture was visually confirmed. The amounts of surface-amorphized FA and curing aid solution used in preparing each self-hardening material were determined so that the mass (parts by mass) of water (dispersion medium) in the self-hardening material (W / B) was the value shown in Tables 3 and 4 below, relative to 100 parts by mass of the surface-amorphized FA in the self-hardening material and the Si-containing compound (amorphous silica or SiO2 in potassium silicate (K2SiO3 aqueous solution)) used as the raw material for the curing aid solution. Each curing aid solution was used 24 hours after preparation.
[0101] In preparing the hardening aid solution 11, an aqueous solution of potassium silicate (K2SiO3) was used as the compound containing the Si element, which was the raw material, and the mass value of SiO2 contained therein was used when calculating W / B.
[0102] [Preparation of self-hardening material using untreated fly ash] The hardening aid solution 6 obtained above was added to fly ash (untreated fly ash) that had not been mechanochemically treated (average volume particle size: 20 μm, CaO content: 10.1% by mass or less), and the resulting mixture was stirred until a uniform state was visually confirmed, thereby preparing a self-hardening material 6'. Each hardening aid solution was used 24 hours after preparation. The amounts of untreated fly ash and hardening aid solution used in preparing the self-hardening material were determined so that the mass (parts by mass) of water (dispersion medium) in the self-hardening material (W / B) relative to the total mass of the untreated fly ash and the Si-containing compound (amorphous silica) used as a raw material for the hardening aid solution (100 parts by mass) were as shown in Tables 3 and 4.
[0103] [Production of hardened body] Each of the self-hardening materials obtained above was poured into a cylindrical formwork with a diameter (inner diameter) of 20 mm and a height of 40 mm, sealed and cured at 40°C for 48 hours, then removed from the formwork and further dried and cured at 40°C for 5 days to obtain a hardened body.
[0104] [Compressive strength of hardened body] The upper and lower end faces of the hardened body were vertically formed, and a uniaxial compression test was performed using a compression testing machine (Shimadzu Corporation, Autograph AG-100KNX) to measure the compressive strength of the hardened body [N / mm 2 The compressive strength was 8 [N / mm 2 If the stability over time of the curing aid solution is high, the uniformity of the composition of the curing aid solution is also high, and the stability over time and uniformity of the composition of the self-hardening material are also high, resulting in a higher compressive strength of the cured product.
[0105] The evaluation results of the compressive strength of the hardened body of each W / B self-hardening material are shown in Table 3 below.
[0106] [Shape change rate of hardened body] The diameter of each of the self-hardening materials obtained above was measured immediately after being poured into a cylindrical formwork with a diameter (inner diameter) of 20 mm and a height of 40 mm using a vernier caliper. The material was then sealed and cured at 40°C for 48 hours, removed from the formwork, and further dried and cured at 40°C for 5 days to obtain a hardened product. The diameter of the hardened product was then measured using a vernier caliper. The shape change rate [%] was calculated using the following formula. The smaller the absolute value of the shape change rate, the better, and a dimensional change rate of 6 [%] or less was considered to be good.
[0107]
number
[0108] The evaluation results of the shape change rate of the hardened self-hardening material of each W / B are shown in Table 4 below.
[0109] [Table 3]
[0110] [Table 4]
[0111] From the results in Tables 1 to 3, the hardening aid solutions 2 to 9 and 11 according to the present invention, which have an alkali molar concentration of 2 mol / kg or more, a dissolution concentration of Si element of 20,000 ppm by mass or more, and a difference in the dissolution concentration of Si element before and after heating and dissolution of 2,000 ppm by mass or less, show a high stability of the dissolution concentration of Si element over time, with the absolute value of the difference between the dissolution concentration of Si element after standing for 1 hour and after standing for 24 hours being 2,900 ppm by mass or less. Furthermore, even when similar tests were conducted with a longer standing time, the dissolution concentration of Si element did not change significantly, and similar results were obtained. Furthermore, it was confirmed that the hardened bodies of self-hardening materials prepared using the hardening aid solutions 2 to 9 and 11 according to the present invention have high compressive strength. When the quality stability of a hardened body is high, the hardened body tends to have higher strength than hardened bodies produced from raw materials of the same composition due to the high uniformity of the composition and physical properties of the hardened body.
[0112] Furthermore, the following experiment was conducted in which the time from preparation of the hardening aid solution to mixing with the object to be hardened in the preparation of the self-hardening material was changed. For hardening aid solution No. 3 according to the present invention, the solution was used 18 days after preparation to prepare a self-hardening material with W / B = 40%, and the compressive strength of the hardened body obtained was measured using the above method. In addition, the solution was used 65 days after preparation to prepare a self-hardening material with W / B = 40%, and the compressive strength of the hardened body obtained was measured using the above method. The compressive strength of the hardened body obtained using hardening aid solution No. 3 18 days after preparation was 28.3 (N / mm 2 ), and the compressive strength of the hardened body obtained using hardening aid solution No. 3 65 days after preparation was 26.1 (N / mm 2 As shown in Table 3 above, the compressive strength of the hardened body obtained using hardening aid solution No. 3 24 hours after preparation was 26.1 (N / mm 2). As described above, it was confirmed that the change in compressive strength of the hardened body of the self-hardening material prepared using hardening assistant solution No. 3 was small even when the time course was different. In other words, it was confirmed that the use of hardening assistant solution No. 3, which has a high temporal stability of the dissolved concentration of Si element, improves the quality stability of the hardened body, also from the viewpoint of improving the temporal stability of the compressive strength of the hardened body of the self-hardening material. Note that, like hardening assistant solution No. 3 according to the present invention, it is estimated that similar results will be obtained with hardening assistant solutions 2, 4 to 9, and 11 according to the present invention, which have a high temporal stability of the dissolved concentration of Si element.
[0113] On the other hand, the results in Tables 1 and 2 show that for curing aid solutions 12-14, which are outside the scope of the present invention, the absolute differences between the dissolved Si concentrations after 1 hour and 24 hours of standing were 11,200 ppm by mass, 17,600 ppm by mass, and 62,200 ppm by mass, respectively. Furthermore, for curing aid solution 15, which is outside the scope of the present invention, the viscosity increased, and the Si concentration became so high that it was impossible to accurately measure the dissolved Si concentration after 24 hours of standing. This confirmed poor stability of the dissolved Si concentration over time. It is believed that curing aid solutions 12-15 exhibited high stability of the dissolved Si concentration over time, and that residual Si-containing compounds remained. The presence of residual Si compounds reduces the uniformity of the composition of the curing aid solution and the self-hardening material, which in turn reduces the uniformity of the composition and physical properties of the cured body, resulting in reduced strength. Furthermore, when the time from preparation of the hardening aid solutions 12 to 15 until mixing with the object to be hardened in the preparation of the self-hardening material is changed, the physical properties such as compressive strength of the hardened self-hardening material produced using these solutions will also change, clearly resulting in poor quality stability.
[0114] Furthermore, from the results of Tables 1 to 3 above, it was confirmed that although hardening aid solutions 1 and 10, which are outside the scope of the present invention, have good stability over time in the dissolved concentration of Si element, the hardened bodies of self-hardening materials prepared using these solutions have poor compressive strength.
Claims
1. Contains an Si element, an alkali, and a dispersion medium; The alkali is an alkali metal hydroxide, The dispersion medium includes water, The dissolved concentration of the Si element measured after leaving the composition to stand for 1 hour in an ambient environment at 25° C. after preparation is 20,000 ppm by mass or more; the molar number of the alkali present in 1 kg of the dispersion medium is 2 mol / kg or more, After preparation, the mixture is allowed to stand for 1 hour in an ambient environment at 25°C, and then diluted twice by mass with a 3 mol / L aqueous KOH solution. The diluted solution is heated at a liquid temperature of 80°C for 5 hours and then allowed to stand for 1 hour in an ambient environment at 25°C. The absolute value of the change in the dissolved concentration of Si element before and after a heat dissolution test is then between 0 ppm by mass and 2000 ppm by mass, The Q3 rate of silicate ions measured after standing for 1 hour in an ambient environment at 25°C after preparation is 0% or more and 45% or less; The Q3 rate is the liquid 29 SiO as measured by Si NMR 4 A peak (Q4) originating from a Si element in which four of the tetrahedral O elements are shared by adjacent Si elements, SiO 4 A peak (Q3) originating from a Si element in which three of the tetrahedral O elements are shared by adjacent Si elements, SiO 4 A peak (Q2) originating from a Si element in which two of the tetrahedral O elements are shared by adjacent Si elements, SiO 4 A peak (Q1) originating from a Si element in which one of the tetrahedral O elements is shared with an adjacent Si element, SiO 4 The ratio of the total area of the peaks (Q0) derived from Si elements in which all of the tetrahedral O elements are not shared with adjacent Si elements to the liquid 29 SiO as measured by Si NMR 4 is the ratio of the area of a peak (Q3) derived from a Si element in which three of the tetrahedral O elements are shared by adjacent Si elements, It is used for hardening a powder including a ceramic powder including at least a surface containing an Si element, The ceramic powder containing Si element at least on its surface includes at least one selected from the group consisting of fly ash, red mud, sewage sludge incineration ash, natural aluminosilicate minerals, calcined products of natural aluminosilicate minerals, volcanic ash, and blast furnace slag. Hardening aid solution.
2. 2. The hardening aid solution according to claim 1, wherein the ceramic powder containing Si element at least on its surface comprises at least one selected from the group consisting of fly ash having an amorphized surface, red mud having an amorphized surface, sewage sludge incineration ash having an amorphized surface, natural aluminosilicate mineral having an amorphized surface, calcined product of natural aluminosilicate mineral having an amorphized surface, volcanic ash having an amorphized surface, and blast furnace slag having an amorphized surface.
3. The hardening assistant solution according to claim 1 or 2, wherein the ceramic powder containing at least Si element on its surface contains fly ash having an amorphized surface.
4. The solution according to any one of claims 1 to 3, wherein the dissolved concentration of the Si element measured after leaving the solution at 25 ° C. for 1 hour is 20,000 ppm by mass or more and 120,000 ppm by mass or less.
5. The curing assistant solution according to any one of claims 1 to 4, wherein the molar number of the alkali present in 1 kg of the dispersion medium is 2 mol / kg or more and 6 mol / kg or less.
6. The curing assistant solution according to any one of claims 1 to 5 and a ceramic powder containing an Si element at least on the surface thereof, The ceramic powder containing Si element at least on its surface includes at least one selected from the group consisting of fly ash, red mud, sewage sludge incineration ash, natural aluminosilicate minerals, calcined products of natural aluminosilicate minerals, volcanic ash, and blast furnace slag. Self-hardening material.
7. 7. The self-hardening material according to claim 6, comprising a powder having a CaO content of 0 mass % or more and 15 mass % or less, the powder comprising a ceramic powder containing elemental Si at least on a surface thereof.
8. A method for producing a hardened body, comprising hardening the self-hardening material according to claim 6 or 7.
9. The method includes mixing a compound containing Si element with an alkali solution containing water, the alkali being a hydroxide of an alkali metal and having a molar number of 2 mol / kg or more in 1 kg of a dispersion medium, to obtain a mixed solution, The compound containing Si element includes at least one selected from the group consisting of silicon element, oxides containing silicon, nitrides containing silicon, carbides containing silicon, oxynitrides containing silicon, carbide nitrides containing silicon, oxycarbide nitrides containing silicon, silicic acid, and silicates. The method for producing the curing assistant solution according to any one of claims 1 to 5.
10. The method for producing a curing assistant solution according to claim 9, further comprising heating the mixed solution at a liquid temperature of 80° C. to 100° C. for 5 hours to 24 hours.
11. A method for producing a curing coagent solution, comprising: The curing assistant solution contains a Si element, an alkali, and a dispersion medium, The alkali is an alkali metal hydroxide, The dispersion medium includes water, The curing aid solution has a dissolved concentration of the Si element of 20,000 ppm by mass or more, as measured after being left to stand for 1 hour in an ambient environment at 25° C. after preparation, The curing assistant solution has a molar number of the alkali present in 1 kg of the dispersion medium of 2 mol / kg or more, The curing aid solution is prepared, left to stand for 1 hour in an ambient environment at 25°C, and then diluted twice by mass with a 3 mol / L aqueous KOH solution. The solution is heated at a liquid temperature of 80°C for 5 hours and then left to stand for 1 hour in an ambient environment at 25°C. The absolute value of the change in the dissolved concentration of Si element before and after a heat dissolution test is then 0 ppm by mass or more and 2000 ppm by mass or less. It is used for hardening a powder including a ceramic powder including at least a surface containing an Si element, The ceramic powder containing Si element at least on the surface thereof includes at least one selected from the group consisting of fly ash, red mud, sewage sludge incineration ash, natural aluminosilicate minerals, calcined products of natural aluminosilicate minerals, volcanic ash, and blast furnace slag; The manufacturing method includes: obtaining a mixed solution by mixing a compound containing Si element with an alkali solution containing water and having an alkali having a molar number of 2 mol / kg or more in 1 kg of a dispersion medium, the alkali being a hydroxide of an alkali metal; Heating the mixed solution at a liquid temperature of 80° C. or more and 100° C. or less for 5 hours to 24 hours; Including, The compound containing Si element includes at least one selected from the group consisting of simple silicon, an oxide containing silicon, a nitride containing silicon, a carbide containing silicon, an oxynitride containing silicon, a carbide nitride containing silicon, an oxynitride carbide containing silicon, silicic acid, and a silicate; A method for producing a curing aid solution.
12. The method for producing a hardening assistant solution according to claim 11, wherein the ceramic powder containing at least Si element on its surface includes at least one selected from the group consisting of fly ash having an amorphized surface, red mud having an amorphized surface, sewage sludge incineration ash having an amorphized surface, natural aluminosilicate mineral having an amorphized surface, calcined product of natural aluminosilicate mineral having an amorphized surface, volcanic ash having an amorphized surface, and blast furnace slag having an amorphized surface.
13. The method for producing a hardening assistant solution according to claim 11 or 12, wherein the ceramic powder containing at least Si element on a surface thereof contains fly ash having an amorphized surface.
14. The method for producing a curing assistant solution according to any one of claims 11 to 13, wherein the dissolved concentration of the Si element measured after leaving the solution at 25 ° C. for 1 hour is 20,000 ppm by mass or more and 120,000 ppm by mass or less.
15. The method for producing a curing assistant solution according to any one of claims 11 to 14, wherein the number of moles of the alkali present in 1 kg of the dispersion medium is 2 mol / kg or more and 6 mol / kg or less.
16. The method for producing a curing assistant solution according to any one of claims 9 to 15, wherein the compound containing Si element is amorphous silica.
17. The method for producing the curing assistant solution according to any one of claims 9 to 16, which does not include mixing an alkali metal silicate or a Group 2 metal silicate.
18. Providing a curing aid solution according to any one of claims 1 to 5 or producing a curing aid solution by a method according to any one of claims 9 to 17; mechanochemically treating ceramic powder containing at least a surface of an Si element; Mixing the prepared hardening assistant solution or the manufactured hardening assistant solution with the ceramic powder after the mechanochemical treatment; Including, The ceramic powder containing Si element at least on its surface includes at least one selected from the group consisting of fly ash, red mud, sewage sludge incineration ash, natural aluminosilicate minerals, calcined products of natural aluminosilicate minerals, volcanic ash, and blast furnace slag. A method for producing a self-hardening material.
19. The method for producing a self-hardening material according to claim 18, further comprising mixing the prepared hardening assistant solution or the produced hardening assistant solution with the ceramic powder after the mechanochemical treatment, and then further mixing an aggregate.
20. The method for producing a self-hardening material according to claim 18 or 19, wherein the self-hardening material includes a powder having a CaO content of 0 mass% or more and 15 mass% or less, and the powder includes a ceramic powder including Si element at least on the surface.
21. Preparing a self-hardening material according to claim 6 or 7, or producing a self-hardening material according to a method for producing a self-hardening material according to any one of claims 18 to 20; hardening the prepared or manufactured self-hardening material; A method for producing a cured body, comprising:
Citation Information
Patent Citations
Substrate for rectifier of ac synchronous generator and method for forming insulation layer thereon
JP1997168280A
Quality-evaluating method of abrasive material particle, polishing method, and abrasive material for polishing glass
JP2004219391A
Method for manufacturing self-hardening material
JP2015218070A
Porous geopolymer hardened body
JP2016135723A
Method of producing hardened body
JP2016222528A